KESALAHAN PEMBENTUKAN KATA PADA TEKS DESKRIPTIF SISWA SMA GENTA SYAPUTRA - Ditha Puteri Tiara Maghfiroh; Deasy Wahyu Hidayati (Universitas Negeri Makassar, 2023)
The purpose of this study was to identify grammatical errors when writing descriptive texts for class X SMA Genta Syaputra. This research is descriptive and qualitative in nature. The source of the data collected is the work of students, namely writing descriptive text. This research data collection technique uses the results of observation. Material analysis was carried out by writing descriptive text which became the subject of the overall research in the analysis of word formation errors. This descriptive text for class X SMA Genta Syaputra is the result of a word formation error, namely an affixation error in the description text for class X SMA Genta Syaputra. It is known that there are errors in 3 parts of the affixation, one of which is the use of infix errors 8, the use of prefix errors 20, and the use of 7 errors in suffixes.